KONSEP JAMINAN PERLINDUNGAN TERHADAP PENGAMBILALIHAN INVESTASI ASING BERDASARKAN HUKUM KEBIASAN INTERNASIONAL DAN IMPLEMENTASINYA DI INDONESIA - Pratomo, Hantoro Widyo (UNES Law Review, 2023)
Foreign capital has become a popular topic in the world of international business. Its presence in the recipient country is considered to bring many benefits to the country. Foreign capital can create new jobs, which can help solve the unemployment problem in the recipient country. The influx of foreign capital also brings new technologies that are not mastered by developing countries. With the influx of foreign investment, it is expected that technology that is generally controlled by developed countries can also be controlled by developing countries through the transfer of knowledge. However, the positive impacts brought by foreign capital do not always benefit the recipient country. Sometimes, foreign investment also has a negative impact on the recipient country. In the viewpoint of International Law, foreign capital needs to be protected. This aims to ensure that foreign capital can operate safely and is protected from various regulations or laws that can harm them. However, this protection should not be done without regard to human rights and the welfare of local communities. In this case, the recipient country must take appropriate measures to ensure that foreign capital companies do not violate human rights and have a positive impact on local communities. In addition, recipient countries must also ensure that they have clear and enforceable laws to protect the rights of local communities.